The geographical distance between producers and consumers of the organic street markets: The case of Belo Horizonte, Brazil - Isabela Kopperschmidt de Oliveira; Leise Kelli de Oliveira; Maria Rosa Amorim Faria Lisboa; Ellen Caroline Nunes Madalon; Luiza Fleury de Freitas; Augusto Cezar Peres Filho (Logistics, 2021)
The organic street markets are considered a short food supply chain, and their importance gained new proportions since COVID-19 brought difficulties to the traditional supply chain. The organic street markets represent a place to sell the product for organic family farmers and an opportunity to obtain better quality and variety of organic products at a lower price. This work aimed to analyze the geographical distance from producers and consumers of organic street markets in Belo Horizonte, Brazil, identifying the organic street market characteristics that influence the organic consumers. The research methods used descriptive statistics, a chi-squared test, and the measurement of the geographical distance. Results allowed us to conclude the organic street markets with more producers attract more consumers and consumers willing to travel long distances. Additionally, the factors related to a street market location, product, and consumer behavior are associated. Finally, results indicated the location of organic street markets contributes to displacements by non-motorized modes. The results indicated that the organic street market characteristics can contribute to a sustainable, short, organic food supply chain in Belo Horizonte.
Keywords: 650; consumers; organic food; organic street market; producers; short supply chain; spatial analysis